Implementation of Teaching Skills Enhancement Through Play Environment Organization in Early Childhood Education - Barokah, Najjah; Yuliantina, Irma (STAI Miftahul Ula Nganjuk, 2024)
The organization of play environments plays a crucial role in facilitating effective teaching and learning processes in early childhood education (ECE). This study explores the impact of well-structured play environments on the development of teaching skills in Quran Kindergarten teachers. The research employed a qualitative approach using interviews, observations, and document analysis to assess the effectiveness of the play environment in enhancing teacher competencies. Findings indicate that while teachers demonstrated a moderate improvement in their teaching skills through the organized play environment, further enhancements in teacher involvement, collaboration, and engagement are needed. This paper emphasizes the importance of a well-organized play environment that caters to the developmental needs of children and its role in shaping effective teaching practices. The study concludes with recommendations for improving teacher training programs and environmental planning to optimize learning outcomes in early childhood settings.